PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN SISWA DALAM MENGAMBIL KEPUTUSAN DI KELAS VII SMP - Intannani Mustikasari; Endang Susantini; Wasis Wasis (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aims to produce the teaching materials based on  science cooperative Group Investigation model which is valid, practical, and effective to facilitate the students decision making skill. The development of teaching material used the 4-D model  and was implemented in 7th-B grade of SMPN 6 Surabaya in the first  semester of  2015/2016 by using the Pre-Experimental One-Group Pretest-Posttest Design. The data collection used validation, observation, quetionnaires, test, and documentation. The data analysis techniques used quantitative and qualitative descriptive analysis.The results of this research are:(1) Teaching material developed to be use consisted of Syllabus, Lesson Plan, Book, Student Worksheet and Test of student learning outcomes are valid; (2) The practicality of teaching material categorized in terms of: (a) The teaching materials categorized in  feasibility of lesson plan, (b) The legibility of the student book;(c) The constraints encountered obstacles during the implemantion and (3) The teaching material effectiveness in terms of: (a) Improving students learning decision making skill by getting gain score in medium category; (b) Improving students learning achievement by getting score in medium catagory; (c) The students give a positive responses toward teaching material and implementation of teaching material developed . Thus, teaching materials based on science cooperative Group Investigation model are valid, practical, and effective to facilitate the students scientific decision making skill in VII grade of Junior High School. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran IPA model kooperatif tipe Group Investigation yang valid, praktis dan efektif untuk meningkatkan keterampilan siswa dalam mengambil keputusan. Pengembangan perangkat pembelajaran menggunakan model 4-D  dan diujicobakan di Kelas VII-B SMPN 6 Surabaya pada semester ganjil tahun ajaran 2015/2016 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode validasi, observasi, angket, dokumentasi, dan tes. Teknik analisis data menggunakan analisis deskriptif kuantitatif dan kualitatif. Hasil penelitian ini menunjukkan: (1) Perangkat pembelajaran yang dikembangkan meliputi Silabus, RPP, Bahan Ajar Siswa, LKS, dan Lembar Penilaian berkategori valid; (2) Perangkat pembelajaran berkategori praktis ditinjau dari: (a) Keterlaksanaan RPP, (b) Keterbacaan bahan ajar siswa, (c) Kendala-kendala yang dijumpai selama proses KBM; serta (3) Perangkat pembelajaran telah efektif ditinjau dari: (a) Peningkatan nilai keterampilan siswa dalam mengambil keputusan siswa dengan perolehan skor n-gain pada kategori sedang, (b) Peningkatan nilai pengetahuan dengan perolehan skor n-gain pada kategori sedang, (c) Siswa merespon positif perangkat yang dikembangkan dan implementasinya. Berdasarkan hasil analisis data dapat disimpulkan bahwa perangkat pembelajaran IPA model kooperatif tipe Group Investigation yang digunakan valid, praktis, dan efektif untuk meningkatkan keterampilan siswa dalam mengambil keputusan di kelas VII SMP